William Worcestre, Sir John Fastolf and Latin Learning - Rundle, David (Library, 2024)
Abstract Sir John Fastolf is known for his association with books in the vernaculars of French and English. It is, though, known that there was also an interest in Latin learning in his circle, and this article provides new evidence concerning that. It introduces a set of manuscripts which passed from the hands of Fastolf’s secretary, William Worcestre, to the foundation of Magdalen College, Oxford. Their passage to Oxford is placed in the context of the battle over Fastolf’s will, with its desire to establish a college at his house of Caister in Norfolk. A college did not necessarily imply a learned function but what Worcestre perceived to be the intentions for that foundation are placed in a wider context of his belief in his late master’s interest in promoting Latin education.